2013
DOI: 10.1152/ajpheart.00445.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sympathetic innervation and PGP9.5 expression by cardiomyocytes after myocardial infarction: effects of central MR blockade

Abstract: Drobysheva A, Ahmad M, White R, Wang H, Leenen FH. Cardiac sympathetic innervation and PGP9.5 expression by cardiomyocytes after myocardial infarction: effects of central MR blockade. Am J Physiol Heart Circ Physiol 305: H1817-H1829, 2013. First published October 11, 2013; doi:10.1152/ajpheart.00445.2013.-Central mechanisms involving mineralocorticoid receptor (MR) activation contribute to an increase in sympathetic tone after myocardial infarction (MI). We hypothesized that this central mechanism also contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Rats in the sham-operated group underwent intracerebroventricular cannulation surgery only, without implantation of a minipump. At the end of the infusion period, left ventricle (LV) dimensions and function were assessed by echocardiography and a Millar catheter, as described previously (9); then tissues were collected to measure the same parameters as in protocol 1.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Rats in the sham-operated group underwent intracerebroventricular cannulation surgery only, without implantation of a minipump. At the end of the infusion period, left ventricle (LV) dimensions and function were assessed by echocardiography and a Millar catheter, as described previously (9); then tissues were collected to measure the same parameters as in protocol 1.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…To date, only a few studies have assessed the role of UCHL1 in heart diseases. One study found that UCHL1 was markedly upregulated in post-MI heart 26 and another suggested that UCHL1 acts as a regulator of the Ang II-induced atrial fibrillation and inhibition of it attenuated atrial fibrosis in vivo 27 . Inspired by the finding that the UCHL1 exerts both endogenous and exogenous pro-activation effects in hepatic stellate cells, which are a type of fibroblast 28,29 , we hypothesised that UCHL1 may promote cardiac fibrosis following MI via induction of CF activation.…”
mentioning
confidence: 99%
“…1 A ), which is then translated to repolarization alternans via the Na + /Ca 2+ exchanger and other Ca 2+ -sensitive currents ( 31 ). However, remodeling in the BZ is complex, involving electrophysiological changes ( 42 ), cellular decoupling ( 47 ), and acute sympathetic denervation followed by sympathetic hyperinnervation ( 3 , 12 ). The exact electrophysiological mechanisms determining how MI promotes alternans formation as well as the potential regulatory effects of sympathetic stimulation remain incompletely understood.…”
mentioning
confidence: 99%